Method for Determining Spontaneous Combustion Risk in Roof Cutting Gob-Side Entry Retaining U + L Ventilation Goaf for Mining Safety - Zongxiang Li; Dongjie Hu; Yu Liu; Yuhang Li; Chuntong Miao (Geofluids)
It is difficult to accurately determine the risk of spontaneous combustion in the U + L ventilation goaf of the first mining face when using the method of roof cutting gob-side entry retaining (RCGSER). To address this problem, the I2101 working face of Qipanjing Mine was considered as the research object in this study. Laboratory experiments, field measurements, and CFD numerical simulation were used to study the continuous oxygen consumption characteristics of coal samples and the distribution of spontaneous combustion danger areas in U + L goaf. The results showed that the oxygen consumption capacity of the coal samples was weak. The continuous oxygen consumption rate of the coal samples had a negative exponential distribution, and the oxygen volume fraction in the smothering zone (critical) was 15%. Furthermore, the three likely areas for spontaneous combustion in the RCGSER goaf were near the open-off cut, within 5–10 m near the RCGSER roadway, and behind the working face. Additionally, the relationship between the dangerous area (Sf) and the different positions (x) of the working face was expressed as Sf=a+b⋅expc⋅xb<0,c<0. On this basis, the fire prevention and extinguishing measures of nitrogen injection was recommended near the open-off cut as well as inhibitor injection at the RCGSER roadway. Because the maximum width of the spontaneous combustion oxidation zone in Qipanjing Mine is 80 m and the minimum daily advancing speed is 1.2 m, spontaneous combustion risk did not exist. This research slightly fills the theoretical gap in the relatively new field of fire prevention in RCGSER goaf.